2018
DOI: 10.1007/s11356-018-2536-7
|View full text |Cite
|
Sign up to set email alerts
|

Antialgal effects of α-linolenic acid on harmful bloom-forming Prorocentrum donghaiense and the antialgal mechanisms

Abstract: Harmful algal blooms (HABs) induced by Prorocentrum donghaiense occur frequently and cause a serious threat to the marine ecosystem. In this study, antialgal effects of α-linolenic acid (ALA) that is generally extracted from diverse macroalga on P. donghaiense were investigated. Specifically, the growth, cellular morphology and ultrastructure, reactive oxygen species (ROS) content, mitochondrial membrane potential (MMP), cytochrome C (Cyt-C), and caspase-9,3 activity of untreated and treated P. donghaiense wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Accordingly, the search for an ecofriendly alternative approach based on the isolation of new bioactive molecules with potent effects against toxic cyanobacteria especially M. aeruginosa becomes an important issue in the field of water environment protection. The use of natural products is now emerging as one of the leading solution to prevent the development of microalgae (Li et al, 2016;Tazart et al, 2018;Wang et al, 2018;Zerrif et al, 2018). The essential oils (EOs) are among natural plant products that are obtained from many aromatic and medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the search for an ecofriendly alternative approach based on the isolation of new bioactive molecules with potent effects against toxic cyanobacteria especially M. aeruginosa becomes an important issue in the field of water environment protection. The use of natural products is now emerging as one of the leading solution to prevent the development of microalgae (Li et al, 2016;Tazart et al, 2018;Wang et al, 2018;Zerrif et al, 2018). The essential oils (EOs) are among natural plant products that are obtained from many aromatic and medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have identified oxidative damage as one of the important allelopathic and toxicological mechanisms of macrophyte allelochemicals on phytoplankton and cyanobacteria (Hong et al ., 2008; Zhao et al ., 2013; Mohamed, 2017; Wang et al ., 2018a; Jiang et al ., 2019; Mowe et al ., 2019; Kang et al ., 2020). In our work, several physiological common indicators have been identified regarding cells responses to the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorella (GY-D25 Chlorella vulgaris) was purchased from Shanghai Guangyu Biological Technology Co., Ltd. and kept in our laboratory, and the diatom was provided by LuoYangtuents Ship Material Research Institute, Qingdao monitoring station. This microalga was cultured in f/2 medium (Guillard 1975) prepared with seawater in a constant temperature incubator at 20 ± 3 °C with cool-white light of 100 μmol photons m –2 s –1 and a light/dark ratio of 12 h/12 h. The cultures were shaken three times per day. , …”
Section: Methodsmentioning
confidence: 99%
“…This microalga was cultured in f/2 medium (Guillard 1975) prepared with seawater in a constant temperature incubator at 20 ± 3 °C with cool-white light of 100 μmol photons m −2 s −1 and a light/dark ratio of 12 h/12 h. The cultures were shaken three times per day. 39,40 2.6.2. Effect of the Complexes on the Growth of Chlorella.…”
Section: Cell Constituents'mentioning
confidence: 99%